Calibration of circular aperture area using vision probe at inmetro - Costa Pedro Bastos; de Oliveira Baldner Felipe; Leta Fabiana Rodrigues (International Journal of Metrology and Quality Engineering, 2016)
Circular aperture areas are standards of high importance for the realization of photometric and radiometric measurements, where the accuracy of these measures is related to the accuracy of the circular aperture area calibrations. In order to attend the requirement for traceability was developed in Brazilian metrology institute, a methodology for circular aperture area measurement as requirements from the radiometric and photometric measurements. In the developed methodology apertures are measured by non-contact measurement through images of the aperture edges captured by a camera. These images are processed using computer vision techniques and then the values of the circular aperture area are determined.